Staging tourism: Performing place - Boyd, Nina; Smitheram, Jan (Interstices: Journal of Architecture and Related Arts, 2019)
This project examines the relationship between architecture and the tourist experience. In architecture, an understanding of the active tourist body is underdeveloped as visuality is often positioned as the dominant mode of analysing tourism. This project mobilizes the tourist by recognising a paradigmatic shift from the”‘gaze” towards “performance”, which privileges the multisensuous experiences of the tourist engaged with architecture. The project investigates how architecture can stage and amplify the performances of tourists in order to produce place, en route. To test this enquiry, a “design through research” methodology is employed where the design proposition is developed through iterative design experiments. The design proposition is explored across three increasing scales, progressing the research through stages of development and refinement. The first experiment engages with the human scale through a 1:1 installation. The next experiment amplifies the practices of performing tourism through the design of a hotel. In the final experiment, the design of an artificial island stages the public performances of tourists.